Anti-fatigue ultra-fine grain dual-phase steel based on phase interface alloy element segregation and manufacturing process of anti-fatigue ultra-fine grain dual-phase steel

By introducing phase interfacial alloy elements into ultrafine crystal double-phase steel to form layered biphase structures and nanocarbides, the problem of performance deterioration of ultrafine crystal steel under low-period fatigue loading is solved, and efficient fatigue resistance improvement is achieved.

CN119876777AActive Publication Date: 2025-04-25XI AN JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510185869.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-25
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

Ultrafine crystalline steel exhibits deterioration of low-period fatigue performance under low-period fatigue loading, resulting in a contradiction between the inability to have both high-period fatigue performance and low-period fatigue performance.

Method used

By introducing phase-interface alloy elements into ultrafine crystal double-phase steel, a layered biphase structure and nanocarbide are formed to stabilize the phase interface and suppress strain localization and fatigue crack propagation rate.

Benefits of technology

The low- and high-period fatigue properties of ultrafine crystalline steel are significantly improved, with yield strength up to 1200~1400MPa, elongation of 20%~25%, fatigue limit is greater than 600MPa, and life under strain-controlled fatigue loading is higher than 1000 weeks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876777A_ABST
    Figure CN119876777A_ABST
Patent Text Reader

Abstract

The invention discloses anti-fatigue ultra-fine grain dual-phase steel based on phase interface alloy element segregation and a manufacturing process of the anti-fatigue ultra-fine grain dual-phase steel. The ultra-fine grain ferrite / martensite dual-phase steel comprises the following chemical components in percentage by weight: 0.2-0.45% of C, 1.5-2.26% of Mn, 1.0-2.0% of Si, 1.0-2.0% of Cr, 0.35-0.39% of Mo, 0.1-0.11% of V, 0.01-1.5% of Al, less than or equal to 0.002% of N, less than or equal to 0.004% of S, less than or equal to 0.02% of P and the balance of Fe. The anti-fatigue ultra-fine grain dual-phase steel has the characteristic of phase interface alloy element segregation, ferrite and martensite are alternately distributed in a lamellar shape to form a lamellar dual-phase structure, the lamellar thickness of the martensite and the ferrite is 0.1-1.0 mu m, and the alloy element segregated at the interface and a carbon element form a nano carbide with a coherent structure with a matrix. According to the method, the phase interface can be stabilized, interface damage in the fatigue loading process can be resisted, strain localization in the fatigue loading process of the ultra-fine grain steel can be inhibited, and the fatigue crack propagation rate can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ultrafine grain steel, and in particular to fatigue-resistant ultrafine grain dual-phase steel based on phase interface alloy element segregation and a manufacturing process thereof. Background Art

[0002] Ultrafine steel is considered an effective means to improve the mechanical properties of materials because its strength can be doubled compared to coarse-grained materials when the grains are refined to the ultrafine or nanocrystalline level. However, in actual engineering applications, fatigue failure accounts for about 90% of the causes of mechanical equipment failures, and fatigue performance is an important indicator that cannot be ignored in the process of material design and development. Through the summary of the research results on the fatigue properties of different ultrafine steels, it is found that under stress-controlled high-cycle fatigue cyclic loading, the fatigue life limit is improved due to the enhanced resistance to fatigue crack initiation of ultrafine and nanocrystalline metals. However, under strain-controlled low-cycle fatigue cyclic loading, the low-cycle fatigue performance of ultrafine and nanocrystalline metals deteriorates significantly, showing a contradiction that high-cycle fatigue performance and low-cycle fatigue performance cannot be achieved at the same time.

[0003] For example, M Okayasu et al. ("Fatigue properties of ultra-fine grained dual-phase ferrite / martensite low carbon steel." International Journal of Fatigue 30.8 (2008): 1358-1365.) prepared ultra-fine grained ferrite / martensite low carbon steel by equal channel angular pressing (ECAP), and the fatigue strength was improved compared with the corresponding coarse grained material. However, due to strain localization during low cycle fatigue loading, its low cycle fatigue performance deteriorated sharply.

[0004] Liu, YX et al. ("Fatigue behaviors of 2205duplex stainless steel with gradient nanostructured surface layer." International Journal of Fatigue 147(2021):106170.) prepared 2205 duplex stainless steel with a gradient nanostructured surface layer by ultrasonic processing. Although its high-cycle fatigue performance was improved, the hard and brittle martensite phase reduced the plasticity of the material, and its low-cycle fatigue life was lower than that of its corresponding coarse-grained material.

[0005] Therefore, how to resolve the two contradictions of ultrafine-grained steel's strength and ductility and high and low-cycle fatigue performance is a very challenging and significant task. Summary of the invention

[0006] In order to overcome the defects of the above-mentioned prior art, the present invention provides a fatigue-resistant ultrafine-grained dual-phase steel based on the segregation of alloy elements at the phase interface and a manufacturing process thereof, wherein the dual-phase steel can stabilize the phase interface, resist interface damage during fatigue loading, inhibit strain localization during fatigue loading of the ultrafine-grained steel and reduce the fatigue crack propagation rate.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A fatigue-resistant ultrafine-grained dual-phase steel based on the segregation of alloy elements at the phase interface. Ferrite and martensite are alternately distributed in lamellar lamellae to form a lamellar dual-phase structure. The average thickness of the martensite and ferrite lamellae is 0.1 to 1.0 μm. The alloy elements C, Cr, Mn and Mo added to the material will be enriched at the interface between the martensite and ferrite phases to form segregation (a local high concentration phenomenon of alloy elements at the interface), and combine with carbon elements to form nano-carbides with a coherent structure with the matrix.

[0009] The coherent nanocarbide can stabilize the interface and resist interface damage during fatigue loading; while the layered dual-phase structure can inhibit strain localization and reduce fatigue crack growth rate during fatigue loading of ultrafine-grained steel, thereby significantly improving the low-cycle and high-cycle fatigue properties of ultrafine-grained steel.

[0010] This layered heterogeneous structure based on the segregation of alloy elements at the phase interface gives the material excellent mechanical properties. The yield strength of the alloy can reach 1200-1400MPa, and the elongation is 20%-25%. Under symmetrical tensile and compressive loading conditions (R=-1), its fatigue limit is greater than 600MPa, and its life is more than 1000 cycles under strain-controlled fatigue loading with a strain amplitude of 0.8%.

[0011] The chemical composition (wt%) of the ultrafine-grained ferrite / martensite dual-phase steel is: C: 0.2-0.45, Mn: 1.5-2.26, Si: 1.0-2.0, Cr: 1.0-2.0, Mo: 0.35-0.39, V: 0.1-0.11, Al: 0.01-1.5, N: ≤0.002, S: ≤0.004, P: ≤0.02, and the rest is Fe.

[0012] A manufacturing process of fatigue-resistant ultrafine-grained dual-phase steel based on phase interface alloy element segregation, comprising the following steps:

[0013] Step 1: Pre-heat treatment

[0014] According to the composition of ultrafine-grained ferrite / martensite dual-phase steel, homogenization annealing is performed to obtain a carbide-free austenite structure, and then forging or rolling into a square billet, and finally quenching is performed to obtain a martensite structure;

[0015] Step 2: Rolling

[0016] The martensitic structure is heated to the ferrite and austenite (α+γ) two-phase region and kept warm, so that the alloy elements C, Cr, Mn and Mo are segregated at the interface between ferrite and austenite; then hot rolling is performed to make the ferrite and austenite distributed in lamellar form along the rolling direction (and the thickness of the ferrite and austenite lamellar layer can be adjusted by adjusting the rolling reduction to achieve structural refinement), and then quenching is performed to obtain an ultrafine-grained ferrite / martensite dual-phase steel with a lamellar structure characteristic;

[0017] Step 3: Tempering

[0018] The ultrafine-grained ferrite / martensite dual-phase steel with a layered structure is tempered to allow the alloy elements and carbon elements concentrated at the interface to form nano-carbides with a coherent structure with the matrix, thereby obtaining fatigue-resistant ultrafine-grained dual-phase steel.

[0019] For the preliminary heat treatment in step 1, it includes the following processes:

[0020] Step 1) Homogenization annealing

[0021] The alloy of the composition is heated to 1200±20°C and then kept warm. The holding time depends on the thickness of the workpiece and is determined at 1-1.5 min / mm. The alloy is then forged into a square billet and then air-cooled to room temperature.

[0022] Step 2) Quenching

[0023] The square billet forged in step 1) is heated to 30 to 50° C. above the Ac3 temperature and quenched to obtain a martensitic structure.

[0024] For the rolling in step 2, it includes the following processes:

[0025] Step 1) Heat treatment before rolling

[0026] The martensite structure is rapidly heated at a speed greater than 2°C / s to a certain temperature in the Ac1-Ac3 temperature range (in the ferrite + austenite two-phase region, and the volume fraction of the austenite phase is controlled at 40-70%) and kept at this temperature for 1-30 minutes, thereby obtaining an alloy having a ferrite / austenite structure with lath characteristics and causing alloy elements to be segregated at the interface;

[0027] Step 2) Warm rolling

[0028] The above-mentioned heat-insulated alloy is hot rolled, and the rolling reduction is controlled between 50% and 85%, so that the lamella orientation is parallel to the rolling direction and the lamella thickness is refined, and the rolled material is immediately quenched to room temperature. During the quenching and cooling process, the lamellar austenite is transformed into martensite, and an ultrafine-grained ferrite / martensite dual-phase steel with alloy elements segregated at the interface between ferrite and martensite and having a layered structure is obtained.

[0029] For the tempering treatment in step 3, the process is:

[0030] The ultrafine-grained ferrite / martensite dual-phase steel with a layered structure prepared in the above process is tempered at 250-300° C. for 1-2 hours, so that the alloy elements and carbon elements concentrated at the interface form nano-carbides with a coherent structure with the matrix.

[0031] Beneficial effects of the present invention:

[0032] 1. The alloy elements and carbon elements segregated at the interface of the fatigue-resistant ultrafine-grained dual-phase steel prepared by the present invention can form nano-carbides with a coherent structure with the matrix. This special structure can stabilize the phase interface and resist interface damage during fatigue loading; and the layered dual-phase structure can inhibit strain localization and reduce fatigue crack growth rate during fatigue loading of ultrafine-grained steel. This unique structure breaks through the technical bottleneck that it is difficult to simultaneously improve the high and low cycle fatigue properties of ultrafine-grained steel.

[0033] 2. The yield strength of the alloy prepared by the present invention can reach 1200-1400MPa, and the elongation is 20%-25%; under the condition of symmetrical tension and compression loading (R=-1), its fatigue limit is greater than 600MPa, and its life is greater than 1000 cycles under strain-controlled fatigue loading with a strain amplitude of 0.8%.

[0034] 3. The fatigue-resistant ultrafine-grained dual-phase steel based on phase interface alloy element segregation described in the present invention has a simple process route, low requirements on production equipment, and is applicable to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 TEM energy spectra of the fatigue-resistant ultrafine-grained dual-phase steel based on phase interface alloy element segregation before and after fatigue loading: (a) before fatigue loading; (b) fatigue failure. DETAILED DESCRIPTION

[0036] The present invention will be further described in detail below in conjunction with the accompanying drawings.

[0037] A manufacturing process of fatigue-resistant ultrafine-grained dual-phase steel based on phase interface alloy element segregation. The implementation steps of the present invention are: firstly, heating the alloy of the selected components to 1200±20°C and determining the holding time according to the thickness of the workpiece at 1-1.5 min / mm, then forging or rolling it into a square billet and air cooling it to room temperature to obtain a carbide-free austenite structure, and reheating the square billet obtained after forging or rolling to 30-50°C above the Ac3 temperature for quenching to obtain a martensitic structure; then rapidly heating the martensitic square billet at a speed greater than 2°C / s to a certain temperature in the Ac1-Ac3 temperature range (in the ferrite+austenite two-phase region, with the volume fraction of the austenite phase controlled at 40-70%) and holding it for 1-30 m in, a ferrite / austenite structure with lath characteristics is obtained, and the alloy elements are segregated at the interface, and then hot rolling is performed, and the cumulative rolling reduction is controlled between 50% and 85%, so that the lamella orientation is parallel to the rolling direction and the lamella thickness is refined, and then the rolled material is immediately quenched to room temperature, and during the quenching cooling process, the lamellar austenite is transformed into martensite; finally, the obtained ultrafine-grained ferrite / martensite dual-phase steel with lamellar structural characteristics is tempered at 250-300° C. for 1-2h, so that the alloy elements and carbon elements segregated at the interface form nano-carbides with a coherent structure with the matrix, so that the ultrafine-grained ferrite / martensite dual-phase steel with alloy elements segregated at the phase interface and having a lamellar structural characteristic can be obtained.

[0038] like Figure 1 As shown in the figure, this layered heterostructure based on the segregation of alloy elements at the phase interface gives the material excellent mechanical properties. The yield strength of the alloy can reach 1200-1400MPa, and the elongation is 20%-25%. Under the conditions of symmetrical tensile and compressive loading (R=-1), its fatigue limit is greater than 600MPa, and its life is higher than 1000 cycles under strain-controlled fatigue loading with a strain amplitude of 0.8%.

[0039] Example 1

[0040] The chemical composition is selected in terms of mass percentage (wt%): C: 0.3, Mn: 1.5, Si: 2.0, Cr: 1.9, Mo: 0.35, V: 0.1, Al: 0.01, N: ≤ 0.002, S: ≤ 0.004, P: ≤ 0.02, and the rest is Fe. The Ac3 and Ac1 temperatures are measured by thermal differential analysis to be 830° C. and 740° C. respectively.

[0041] The alloy of this composition is heated to 1200°C and the holding time is determined according to the thickness of the workpiece at 1.5 min / mm, then it is forged into a square billet and air-cooled to room temperature, and then the forged square billet is reheated to 40°C above the Ac3 temperature and quenched to obtain a martensitic structure; the martensitic square billet is then rapidly heated to 770°C at a rate of 2.2°C / s and kept for 20 minutes, and then it is hot rolled with a cumulative rolling reduction of 85%, and then the rolled material is immediately quenched to room temperature; finally, it is tempered at 300°C for 1h to obtain an ultrafine-grained ferrite / martensite dual-phase steel with a lamellar thickness of 0.1μm, in which the alloy elements are concentrated at the phase interface and have a layered structure characteristic.

[0042] Its mechanical properties are as follows: yield strength can reach 1400MPa, elongation is 24%; under symmetrical tension and compression loading conditions (R=-1), its fatigue limit is 650MPa, and its life is 2000 cycles under strain-controlled fatigue loading with a strain amplitude of 0.8%.

[0043] Example 2

[0044] The chemical composition selected by mass percentage (wt%) is: C: 0.2, Mn: 2.26, Si: 1.0, Cr: 1.01, Mo: 0.39, V: 0.11, Al: 0.7, N: ≤0.002, S: ≤0.004, P: ≤0.02, and the rest is Fe.

[0045] The Ac3 and Ac1 temperatures were measured to be 850℃ and 745℃ respectively by thermal differential analysis. The alloy of this composition was heated to 1220℃ and the holding time was determined according to the thickness of the workpiece at 1.3min / mm, then it was forged into a billet and air-cooled to room temperature, then the forged billet was reheated to 30℃ above the Ac3 temperature and quenched to obtain a martensitic structure; then the martensitic billet was rapidly heated to 785℃ at a speed of 2.5℃ / s and kept for 5min, then hot rolled with a cumulative rolling reduction of 80%, and then the rolled material was immediately quenched to room temperature; finally, it was tempered at 270℃ for 1h20min to obtain an ultrafine-grained ferrite / martensite dual-phase steel with a lamellar thickness of 0.42μm and alloy elements segregated at the phase interface and having a layered structure.

[0046] Its mechanical properties are as follows: yield strength can reach 1370MPa, elongation is 23.4%; under symmetrical tension and compression loading conditions (R=-1), its fatigue limit is 643MPa, and its life is 1800 cycles under strain-controlled fatigue loading with a strain amplitude of 0.8%.

[0047] Example 3

[0048] The chemical composition selected by mass percentage (wt%) is: C: 0.45, Mn: 1.8, Si: 1.5, Cr: 1.5, Mo: 0.36, V: 0.11, Al: 1.2, N: ≤0.002, S: ≤0.004, P: ≤0.02, and the rest is Fe.

[0049] The Ac3 and Ac1 temperatures were measured to be 825°C and 730°C respectively by thermal differential analysis. The alloy of this composition was heated to 1180°C and the holding time was determined according to the thickness of the workpiece at 1.0min / mm, then it was forged into a billet and air-cooled to room temperature, then the forged billet was reheated to 50°C above the Ac3 temperature and quenched to obtain a martensitic structure; then the martensitic billet was rapidly heated to 765°C at a rate of 2.6°C / s and kept for 15min, then hot rolled with a cumulative rolling reduction of 70%, and then the rolled material was immediately quenched to room temperature; finally, it was tempered at 250°C for 2h to obtain an ultrafine-grained ferrite / martensite dual-phase steel with a lamellar thickness of 0.5μm and alloy elements segregated at the phase interface and having a layered structure.

[0050] Its mechanical properties are as follows: yield strength can reach 1355MPa, elongation is 23%; under symmetrical tension and compression loading conditions (R=-1), its fatigue limit is 635MPa, and its life is 1680 cycles under strain-controlled fatigue loading with a strain amplitude of 0.8%.

[0051] Example 4

[0052] The chemical composition selected by mass percentage (wt%) is: C: 0.35, Mn: 2.0, Si: 1.8, Cr: 1.3, Mo: 0.37, V: 0.1, Al: 1.5, N: ≤0.002, S: ≤0.004, P: ≤0.02, and the rest is Fe.

[0053] The Ac3 and Ac1 temperatures were measured to be 815.6°C and 726.5°C by thermal differential analysis. The alloy of this composition was heated to 1190°C and the holding time was determined according to the thickness of the workpiece at 1.4min / mm, then it was forged into a billet and air-cooled to room temperature, then the forged billet was reheated to 25°C above the Ac3 temperature and quenched to obtain a martensitic structure; then the martensitic billet was rapidly heated to 758°C at a rate of 2.3°C / s and kept for 30min, then hot rolled with a cumulative rolling reduction of 50%, and then the rolled material was immediately quenched to room temperature; finally, it was tempered at 280°C for 1h20min to obtain an ultrafine-grained ferrite / martensite dual-phase steel with a lamellar thickness of 1μm and alloy elements concentrated at the phase interface and having a layered structure.

[0054] Its mechanical properties are as follows: yield strength can reach 1203MPa, elongation is 20.3%; under symmetrical tension and compression loading conditions (R=-1), its fatigue limit is 603MPa, and its life is 1025 cycles under strain-controlled fatigue loading with a strain amplitude of 0.8%.

[0055] The present invention proposes a preparation method of fatigue-resistant ultrafine-grained dual-phase steel based on the phase interface alloy element segregation based on the deformation and phase transformation coupling control theory. First, according to the phase equilibrium principle, the temperature range of the ferrite and austenite two-phase region is kept warm. Since the austenite nucleates and grows and the solubility of the alloy elements in the two phases is different, the alloy elements will diffuse into the austenite and stabilize the austenite. At the same time, the segregation of the alloy elements can reduce the transformation temperature of the austenite, so that the austenite preferentially nucleates at the lath martensite and grows along the lath, thereby obtaining a ferrite / austenite structure with lath characteristics and alloy elements segregated at the interface. Secondly, the ferrite and martensite lamellae are oriented parallel to the rolling direction and the lamellae are refined by warm rolling, and then the lamellar austenite is transformed into martensite by quenching and inherits the segregation of alloy elements. Finally, tempering is used to make the alloy elements and carbon elements segregated at the interface form nano-carbides with a coherent structure with the matrix, thereby obtaining fatigue-resistant ultrafine-grained dual-phase steel based on the phase interface alloy element segregation.

[0056] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

Claims

1. A fatigue-resistant ultrafine-grained dual-phase steel based on phase interface alloy element segregation, characterized in that: Ferrite and martensite are alternately distributed in lamellar form to form a lamellar two-phase structure. The average thickness of martensite and ferrite lamellar is 0.1-1.0μm. The alloy elements C, Cr, Mn and Mo added to the material will be enriched at the interface between martensite and ferrite to form segregation, and combine with carbon to form nano-carbides with a coherent structure with the matrix.

2. The fatigue-resistant ultrafine-grained dual-phase steel based on phase interface alloy element segregation according to claim 1, characterized in that: The chemical composition (wt%) of the ultrafine-grained ferrite / martensite dual-phase steel is: C: 0.2-0.45, Mn: 1.5-2.26, Si: 1.0-2.0, Cr: 1.0-2.0, Mo: 0.35-0.39, V: 0.1-0.11, Al: 0.01-1.5, N: ≤0.002, S: ≤0.004, P: ≤0.02, and the rest is Fe.

3. The manufacturing process of the fatigue-resistant ultrafine-grained dual-phase steel based on phase interface alloy element segregation according to claim 2 comprises the following steps: Step 1: Pre-heat treatment According to the composition of ultrafine-grained ferrite / martensite dual-phase steel, homogenization annealing is performed to obtain a carbide-free austenite structure, and then forging or rolling into a square billet, and finally quenching is performed to obtain a martensite structure; Step 2: Rolling The martensitic structure is heated to the ferrite and austenite (α+γ) two-phase region and kept warm, so that the alloy elements C, Cr, Mn and Mo are segregated at the interface between ferrite and austenite; hot rolling is then performed to make the ferrite and austenite distributed in lamellar form along the rolling direction, and then quenching is performed to obtain an ultrafine-grained ferrite / martensite dual-phase steel with a lamellar structure characteristic; Step 3: Tempering The ultrafine-grained ferrite / martensite dual-phase steel with a layered structure is tempered to allow the alloy elements and carbon elements concentrated at the interface to form nano-carbides with a coherent structure with the matrix, thereby obtaining fatigue-resistant ultrafine-grained dual-phase steel.

4. According to the manufacturing process of the fatigue-resistant ultrafine-grained dual-phase steel based on phase interface alloy element segregation according to claim 3, the pre-heat treatment in step 1 comprises the following processes: Step 1) Homogenization annealing The alloy of the composition is heated to 1200±20° C. and then kept warm for a time of 1 to 1.5 min / mm, and then forged into a square billet and air-cooled to room temperature; Step 2) Quenching The square billet forged in step 1) is heated to 30 to 50° C. above the Ac3 temperature and quenched to obtain a martensitic structure.

5. The manufacturing process of fatigue-resistant ultrafine-grained dual-phase steel based on phase interface alloy element segregation according to claim 3, wherein the rolling in step 2 comprises the following processes: Step 1) Heat treatment before rolling The martensite structure is rapidly heated to a certain temperature in the Ac1-Ac3 temperature range at a speed greater than 2°C / s and kept at this temperature for 1-30 minutes, thereby obtaining an alloy having a ferrite / austenite structure with lath characteristics and causing alloy elements to be segregated at the interface; Step 2) Warm rolling The above-mentioned heat-insulated alloy is hot rolled, and the rolling reduction is controlled between 50% and 85%, so that the lamella orientation is parallel to the rolling direction and the lamella thickness is refined, and the rolled material is immediately quenched to room temperature. During the quenching and cooling process, the lamellar austenite is transformed into martensite, and an ultrafine-grained ferrite / martensite dual-phase steel with alloy elements segregated at the interface between ferrite and martensite and having a layered structure is obtained.

6. According to the manufacturing process of fatigue-resistant ultrafine-grained dual-phase steel based on phase interface alloy element segregation according to claim 5, the Ac1-Ac3 temperature range is in the ferrite + austenite two-phase region, and the volume fraction of the austenite phase is controlled at 40-70%.

7. According to the manufacturing process of the fatigue-resistant ultrafine-grained dual-phase steel based on phase interface alloy element segregation according to claim 3, for the tempering treatment in step 3, the process is: The ultrafine-grained ferrite / martensite dual-phase steel with a layered structure prepared in the above process is tempered at 250-300° C. for 1-2 hours.

Citation Information

Patent Citations

  • Ultra-fine grain martensite ferrite dual-phase steel with two-peak ferrite grains distributed and production process of ultra-fine grain martensite ferrite dual-phase steel

    CN107177783A

  • 1.1 GPa-grade lamellar interphase martensite-ferrite dual-phase steel and preparation method thereof

    CN114293111A

  • Mo segregation induction-based superfine heterostructure martensitic steel and heat treatment process thereof

    CN119464940A

  • V-containing cold-rolled dual-phase steel having high strength-ductility product and production method therefor

    WO2024222304A1